The Effect of Polymers Ratio Carboxymethyl Chitosan, Polyvinyl Pyrolidone K-30, and Ethyl Cellulose N22 on Physico-Chemical Characteristics and Drug Release from Matrix Type Diclofenac Potassium Patch - Esti Hendradi; Esti Rahayuningtyas; Tristiana Erawati (Universitas Airlangga, 2023)
Background: Diclofenac potassium is an NSAID drug that is used in the treatment of mild to moderate pain. The use of this drug orally can cause side effects in the gastrointestinal tract, and the drug will undergo extensive first-pass metabolism in the liver. Therefore, preparations for transdermal patches were made. Objective: Determining the effect of the polymer ratios of carboxymethyl chitosan, polyvinyl pyrolidone K-30, and ethyl cellulose N22 on the physicochemical characteristics and drug release of a matrix type diclofenac potassium patch. Methods: In this study, matrix type diclofenac potassium patches were made using a combination of carboxymethyl chitosan (CMC), polyvinyl pyrrolidone (PVP) K-30 polymer, and ethyl cellulose (EC) N22 in a ratio of 2:3:7 and 3:2:7. Patches are made by mixing the entire polymer matrix and diclofenac potassium together, which are then evaporated and dried. Results: The results showed that the different polymer compositions of CMC, PVP K-30, and EC N22 resulted in patches with physicochemical characteristics that were not significantly different. The combination of these polymers is able to control the release of the drug from the patch for a long time. It was also found that increasing the concentration of CMC was able to increase the rate of release of diclofenac potassium. Formula 2 with a ratio of 3:2:7 is claimed to be the best formula in terms of physical, chemical, and drug release characteristics from the patch. Further studies are needed, such as drug penetration tests into the skin.